2000
DOI: 10.1348/014466600164444
|View full text |Cite
|
Sign up to set email alerts
|

Among friends? An examination of friendship and the self‐serving bias

Abstract: Do friends bound each other's self‐enhancement tendencies? Do friends display the self‐serving bias (SSB; i.e. taking individual credit for success but blaming a partner for failure)? Dyads consisting of either friends or strangers engaged in an interdependent‐outcomes creativity test, received bogus success or failure feedback at the dyadic level, and made responsibility attributions for the joint test performance. Strangers displayed the SSB. Friends, in contrast, refrained from the SSB: they shared responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 31 publications
2
51
2
Order By: Relevance
“…People blamed distant others, but not close others, for the dyad's failure: Closeness increased liking, and liking reduced attributions for failure (cf. Campbell, Sedikides, Reeder, & Elliot, 2000). Other research shows that liked others are spared the blame for one's own failure (Silvia & Duval, 2001).…”
Section: Similarity and Reactancementioning
confidence: 99%
“…People blamed distant others, but not close others, for the dyad's failure: Closeness increased liking, and liking reduced attributions for failure (cf. Campbell, Sedikides, Reeder, & Elliot, 2000). Other research shows that liked others are spared the blame for one's own failure (Silvia & Duval, 2001).…”
Section: Similarity and Reactancementioning
confidence: 99%
“…Most notably, friendships extend across time and setting, whereas induced closeness exists only in the short duration of the RCIT (i.e., 9 min) and in the laboratory. (Campbell, Sedikides, Reeder, & Elliot, 2000) Although Reis et al (2011) noted this limitation, they then moved to a task in Study 2 that introduces a different but equally problematic source of induced closeness: online chatting. A large body of research has documented the ways in which the relative anonymity of online communication can lead to "hyperpersonal communication," in which the ambiguity of cues in online communication (a result of the lack of face-to-face contact) leads receivers to overperceive similarity in their partner and then to engage in strategic self-presentation to match that similarity, leading to relationships that become artificially close and intense in a very short period of time (Turner, Grube, & Meyers, 2001;Walther, 1996Walther, , 1997.…”
Section: Are the Paradigms Representative Of Everyday Social Interactmentioning
confidence: 99%
“…As said, research has shown that people are less likely to demonstrate the self-serving bias when the bond with the partner is stronger. When individuals work together with friends rather than strangers, they are more eager to share credit as well as the blame (Campbell et al, 2000).…”
Section: Discussionmentioning
confidence: 99%